(untitled) ("Conference on Universal Science Research 2023", 2024)
External quality assessment (EQA) and Internal Quality control (IQC) are an alternative tool to cross-checking of blood slides in the quality control of malaria microscopy. This study was aimed to check EQA and IQA of malaria microscopy in El Obeid City North Kordofan. A total of 76 laboratories (55%private and 45%public) were participated in the study. A well-designed questionnaire plus five blood films (two negative and three positive films with different parasitaemia; (low, moderate and high) were distributed for each laboratory under study. Two slides (stained and unstained) blood films and one ml of Geimsa stain were collected from each laboratory. The study revealed that, most of laboratories were using Geimsa, but the EQA and IQC for both staff and stain were demonstrated poor performance. Although, only 20% had a record for malaria results, 50% of laboratories reporting only whether the parasite identified or not. 75% were using only thick blood film. The results of the five blood films were; 61% were correct clear negative, 49% were negative with artifacts, while the three positive slides were correctly as follows; low (49%), moderate (76%) and (59%) of high parasite density. The major errors include; not reporting the density of malaria low (50%), moderate (31%) and high parasite (13%), but those reporting wrong were low ( 24%,) moderate (39%) and high parasite (24%). The study concludes that, the EQA and IQC of microscopical examinations for malaria parasite in laboratories in ElObeid were acceptable,further training courses and effective quality assurance scheme were needed.